1990
DOI: 10.1071/pp9900517
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Respiratory Processes and Growth Rate of Selected Australian Alpine and Related Lowland Plant Species

Abstract: Respiratory processes and growth rates of alpine and lowland species of three genera (Ranunculus, Plantago and Luzula) were compared. Relative growth rates were determined for the first 14 weeks of growth at two temperatures (7-10°C and 12-15°C). Generally, the relative growth rates of the alpine species were lower than those of their lowland relatives. Whole-plant respiration rates were measured and leaf slices from each species were used for a detailed analysis of respiratory pathways. Major differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…High-altitude alpine plants, coping in their places of origin with low temperature, strong winds, potentially high radiation levels and reduced partial pressures of CO 2 , were slow growing also in the common garden culture. They appear to be inherently slow-growing Atkin & Day 1990). This may be related to the low specific leaf area values of high-altitude plants (Woodward 1979a(Woodward , b, 1983Körner & Diemer 1987;Atkin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…High-altitude alpine plants, coping in their places of origin with low temperature, strong winds, potentially high radiation levels and reduced partial pressures of CO 2 , were slow growing also in the common garden culture. They appear to be inherently slow-growing Atkin & Day 1990). This may be related to the low specific leaf area values of high-altitude plants (Woodward 1979a(Woodward , b, 1983Körner & Diemer 1987;Atkin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, interspecific studies along altitudinal gradients have shown that species from high altitudes usually have lower RGRs and lower leaf expansion rates than lowland species (Woodward 1979;Körner & Woodward 1987;Atkin & Day 1990;Atkin et al 1996).…”
Section: Temperaturementioning
confidence: 99%
“…proportional change in R with a 10 • C increase in temperature, typically around 2) (e.g. Atkin and Day 1990;Ryan 1991;Raich and Schlesinger 1992). As a result, most simulation models such as Biome-BGC, Century (Schimel et al 1997), PnET (Aber and Federer 1992) and several dynamic vegetation models (White et al 2000;Cramer et al 2001) assume that R responds to short-and long-term changes in temperature in a fixed, exponential manner (Q 10 = 2.0).…”
Section: Introductionmentioning
confidence: 99%